Changing patterns of social media use? A population-level study of Finland - Ilkka Koiranen; Teo Keipi; Aki Koivula; Pekka Räsänen (Springer Link, 2022)
This article examines the changing patterns of Finnish social media use during the years 2008–2016. This is the first temporal look at changes in Finnish social media use with representative population-level data. We assess how social media use has evolved between socio-economic and demographic groups in advanced information societies, with a focus on Finland. We also look at how demographic factors associate with use purposes of social media. The target of empirical analysis is on social media use and use purposes by gender, age, education level and area of residence. The data come from nationally representative and temporally comparable surveys focusing on adult populations. Findings show that the effect of socio-demographic factors on overall use and different use purposes of social media persists. Furthermore, the results seem to show a diminishing of the socializing impact of social media; on the other hand, individual, commercial and goal-oriented use practices seem to have become a major focus of social media use.